Measuring outcomes of a peer-led social communication skills intervention for adults with acquired brain injury: A pilot investigation. Issue 7 (9th August 2021) - Howell, Susan; Beeke, Suzanne; Pring, Tim; Varley, Rosemary
ABSTRACT: Reduced social competence following severe acquired brain injury (ABI) is well-documented. This pilot study investigated a peer-led group intervention based on the claim that peer models may be a more effective mechanism for behaviour change than clinician-led approaches. Twelve participants with severe ABI were recruited from a post-acute neurorehabilitation setting and randomly assigned to either a peer-led intervention or a staff-led activity group (usual care) (Clinicaltrials.gov: NCT02211339). The groups met twice a week for 8 weeks. A peer was trained separately to facilitate interaction in the intervention group. Training comprised 16 individual sessions over 4 weeks. Group behaviour was measured twice at baseline, after intervention and at maintenance (4 weeks), using the Adapted Measure of Participation in Conversation (MPC) and the Interactional Network Tool (INT), a newly devised measure of group conversational interaction. Outcome measures showed differential sensitivity. The groups did not differ in baseline behaviour. Findings showed a significant improvement in the treated group on the MPC transaction scale post-intervention ( p = .02). The intervention group showed more balanced interaction post-intervention on the INT and at follow-up. Findings show preliminary evidence of the advantage for peer-led groups. The INT shows promise as a method to detect a change in group communication behaviour. Trial registration: ClinicalTrials.gov identifier: NCT02211339.